The therapeutic effect of habit reversal training for Tourette syndrome: a meta-analysis of randomized control trials. (1st November 2020) - Yu, Liping; Li, Ying; Zhang, Jishui; Yan, Chunmei; Wen, Fang; Yan, Junjuan; Wang, Fang; Liu, Jingran; Cui, Yonghua
ABSTRACT: Objectives: Comprehensive behavioral intervention for tics (CBIT) and habit reversal training (HRT) are forms of cognitive behavioral therapy that can effectively reduce tic symptoms in patients with tic disorders, but their efficacies and potential moderators were needed to be clarified. Methods: In the present study, a meta-analysis was performed to identify the efficacy of HRT and CBIT for individuals with tic disorders. The standard mean difference (SMD) was calculated to assess the effect size of the efficacy of HRT. Subgroup analysis and meta-regression analysis were performed to identify the potential heterogeneity of the SMD of HRT. Results: A total of 10 randomized controlled trials (RCTs) including 586 patients with tic disorders were identified. The pooled SMD was −0.43 (95% CI: −0.71, −0.16). The effect size of HRT was moderated by different 'Comparison Conditions' (it means the different behavioral therapies in the control group). Conclusion: Overall, the authors found a small to medium effect size for the efficacy of HRT. As the most promising behavioral therapy, they conclude that HRT is effective for the treatment of patients with tic disorders. Further high-quality RCTs are needed to determine the efficacy of HRT compared with that of medications.